Resistance Training With Ankle Weight Cuffs Is Feasible in Patients With Acute Exacerbation of COPD. Issue 1 (January 2017) - Kofod, Linette Marie; Døssing, Martin; Steentoft, Johnna; Kristensen, Morten Tange
Abstract : PURPOSE: Quadriceps muscle weakness is a serious complication of physical inactivity following hospitalization due to acute exacerbations of chronic obstructive pulmonary disease (AECOPD). Preventing strength loss during AECOPD is therefore a high priority. We aimed to evaluate the feasibility of progressive knee-extension resistance training, using ankle weight cuffs on patients with AECOPD, based on prespecified criteria for feasibility. METHODS: Thirty-four patients (18 men, mean age 74 years, forced expiratory volume in 1 second = 33% predicted) with AECOPD participated in daily knee-extension strength training. During training, the patients were seated on the bedside and performed 3 sets of 10-repetition maximum loads, using ankle weight cuffs. The primary outcome was the change in load from the first to last training sessions. The secondary outcomes were changes in maximal isometric knee-extension strength, the Sit-to-Stand (STS) and Timed Up and Go (TUG) tests. RESULTS: The training load increased progressively by a mean (standard deviation) of 54% ± 41% (when calculated on an individual basis), from a mean of 6.5 ± 3.3 to 9.2 ± 3.5 kg over the course of 5.6 ± 2.3 training days ( P < .001). Knee-extension strength improved by a mean of 12% ( P = .02), whereas the TUG and STS test performances improved by 11% ( P = .001) and 19% ( P = .03), respectively. Ninety-eight percent of the planned training sessions were completed with no side effects. CONCLUSIONS: Progressive resistance training with ankle weight cuffs is feasible in patients who are severely disabled due to AECOPD. The approach is simple and seems to counteract the loss of muscle strength and function during hospitalization. Abstract : To prevent muscle strength loss during hospitalization, 34 patients with acute exacerbations of chronic obstructive pulmonary disease proved that daily progressive knee-extension resistance training using ankle weight cuffs is feasible and seems to counteract the loss of strength and function. No side effects of the training were reported.